MÍDIA ELETRÔNICA, CONTROLE SOCIAL E PODER ECONÔMICO: particularidades da concessão da TV Difusora/Rede Globo no Maranhão - DOUGLAS, Franklin (2011)
The television s electronic media as an instrument of social control and economic power from the analysis of the dispute the right of retransmission of TV Globo in Maranhão. Relying on the theoretical assumption of marxist Political Economy of Communication and Social Control category, investigates the relationship between media, democracy and economic power, taking as an example how the oligarchy Sarney has been using the television as a tool of political and economic power concentration, particularly considering the making of the retransmission of TV Globo in Maranhão of Difusora, in possession of the family Bacelar, by TV Mirante, ownership of the family Sarney.